Lessons Learned From Early Implementation Stage of Accrual Accounting in Indonesia Local Government. A Case Study in Local Government of Province Jawa Timur - Irwan Taufiq Ritonga (The Indonesian Journal of Accounting Research, 2016)
Abstract:Starting from 1 January 2015, all local governments in Indonesia implement accrual accounting.  There is a big question as of how good the implementation. Therefore, the objective of this study is to assess the implementation of accrual accounting in a local government in Indonesia for the first three months. This study utilizes descriptive-qualitative research method. This study finds that almost all of the working unit in the local government has not implemented the accrual accounting properly because the implementation is not conformed to the Government Accounting Standards. However, the local government showed a tendency to improvement. Problems in the implementation involved inadequatehuman resourcecapacity, poor commitment and poor intention of leaders of local government working units to implement accrual accounting, the poor infrastructure of accrual accounting, and poor organizational and internal coordination of local government working unit. Findings of this study will contribute benefits to other local governments by learning the successful critical variables in implementing accrual accounting.  Based on results, the central government (i.e., the Ministry of Home Affairs), local government executives could utilize the evidence to improve the implementation of accrual accounting for the future time. For Indonesian scholars and practitioners in the field of public sector accounting, this study will represent the first attempt to assess the implementation of accrual accounting in Indonesia.Abstrak: Mulai dari 1 Januari 2015, semua pemerintah daerah di Indonesia menerapkan akuntansi akrual. Ada pertanyaan besar tentang seberapa bagus implementasinya. Oleh karena itu, tujuan dari penelitian ini adalah untuk menilai penerapan akuntansi akrual di pemerintah daerah di Indonesia selama tiga bulan pertama. Penelitian ini menggunakan metode penelitian deskriptif-kualitatif. Studi ini menemukan bahwa hampir semua unit kerja di pemerintah daerah belum menerapkan akuntansi akrual dengan baik karena pelaksanaannya tidak sesuai dengan Standar Akuntansi Pemerintah. Namun, pemerintah daerah menunjukkan kecenderungan untuk perbaikan. Masalah dalam implementasi melibatkan kapasitas sumber daya manusia yang tidak memadai, komitmen yang buruk dan niat buruk dari pemimpin  unit kerja pemerintah daerah untuk menerapkan akuntansi akrual, infrastruktur buruk akuntansi akrual, dan koordinasi organisasi dan internal yang buruk dari unit kerja pemerintah daerah. Temuan dari studi ini akan memberikan manfaat bagi pemerintah daerah lainnya dengan mempelajari variabel kritis yang berhasil dalam menerapkan akuntansi akrual. Berdasarkan hasil, pemerintah pusat (yaitu, Departemen Dalam Negeri), eksekutif pemerintah lokal dapat memanfaatkan bukti untuk meningkatkan pelaksanaan akuntansi akrual untuk waktu mendatang. Bagi para sarjana dan praktisi Indonesia di bidang akuntansi sektor publik, penelitian ini akan mewakili upaya pertama untuk menilai penerapan akuntansi akrual di Indonesia.Abstract:Starting from 1 January 2015, all local governments in Indonesia implement accrual accounting.  There is a big question as of how good the implementation. Therefore, the objective of this study is to assess the implementation of accrual accounting in a local government in Indonesia for the first three months. This study utilizes descriptive-qualitative research method. This study finds that almost all of the working unit in the local government has not implemented the accrual accounting properly because the implementation is not conformed to the Government Accounting Standards. However, the local government showed a tendency to improvement. Problems in the implementation involved inadequatehuman resourcecapacity, poor commitment and poor intention of leaders of local government working units to implement accrual accounting, the poor infrastructure of accrual accounting, and poor organizational and internal coordination of local government working unit. Findings of this study will contribute benefits to other local governments by learning the successful critical variables in implementing accrual accounting.  Based on results, the central government (i.e., the Ministry of Home Affairs), local government executives could utilize the evidence to improve the implementation of accrual accounting for the future time. For Indonesian scholars and practitioners in the field of public sector accounting, this study will represent the first attempt to assess the implementation of accrual accounting in Indonesia. Keywords: local government, accrual accounting Abstrak:Mulai dari 1 Januari 2015, semua pemerintah daerah di Indonesia menerapkan akuntansi akrual. Ada pertanyaan besar tentang seberapa bagus implementasinya. Oleh karena itu, tujuan dari penelitian ini adalah untuk menilai penerapan akuntansi akrual di pemerintah daerah di Indonesia selama tiga bulan pertama. Penelitian ini menggunakan metode penelitian deskriptif-kualitatif. Studi ini menemukan bahwa hampir semua unit kerja di pemerintah daerah belum menerapkan akuntansi akrual dengan baik karena pelaksanaannya tidak sesuai dengan Standar Akuntansi Pemerintah. Namun, pemerintah daerah menunjukkan kecenderungan untuk perbaikan. Masalah dalam implementasi melibatkan kapasitas sumber daya manusia yang tidak memadai, komitmen yang buruk dan niat buruk dari pemimpin unit kerja pemerintah daerah untuk menerapkan akuntansi akrual, infrastruktur buruk akuntansi akrual, dan koordinasi organisasi dan internal yang buruk dari unit kerja pemerintah daerah. Temuan dari studi ini akan memberikan manfaat bagi pemerintah daerah lainnya dengan mempelajari variabel kritis yang berhasil dalam menerapkan akuntansi akrual. Berdasarkan hasil, pemerintah pusat (yaitu, Departemen Dalam Negeri), eksekutif pemerintah lokal dapat memanfaatkan bukti untuk meningkatkan pelaksanaan akuntansi akrual untuk waktu mendatang. Bagi para sarjana dan praktisi Indonesia di bidang akuntansi sektor publik, penelitian ini akan mewakili upaya pertama untuk menilai penerapan akuntansi akrual di Indonesia.